Effects of Outdoor Conditions on the Compound Parabolic Concentrator Performance (The International Journal of Engineering & Information Technology (IJEIT), 2024)
In this study, the effect of outdoor conditions(wind velocity and ambient temperature) on the thermalefficiency of a non-evacuated Compound ParabolicConcentrator solar collector (CPC) was investigated fortwo different flow rates. Matlab program was built, andsimulation results for different outdoor conditions werecompared with an actual outdoor data set that was takenat Misurata city, Libya. Although this study showed someeffects of outdoor conditions on the CPC collectorcomponent’s temperatures and heat losses, no importantinfluence on the collector efficiency was noticed.Therefore, even though wind velocity and ambienttemperature vary throughout the day, approximatingthem as constant values is a reasonable assumption. Massflow rate is the most important parameter that affects theCPC efficiency.